2011
DOI: 10.1007/s11033-011-0752-z
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of p16 (CDKN2A) and RB1 polymorphisms with susceptibility to cervical cancer in Indian population

Abstract: The potent tumor suppressors P16 and RB1 are the key regulators of cell cycle machinery in eukaryotes. Polymorphisms in these genes play an important role in the outcome of various diseases including cancer. In the present study, we evaluated the association of p16 and RB1 polymorphisms with cervical cancer susceptibility in Indian population. We screened 150 histologically confirmed cervical cancer cases along with equal number of healthy controls with normal cervical cytology. PCR-RFLP method was employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…However, further studies elucidating the downstream effects of this polymorphism are warranted. The effect of RB1 polymorphisms on the susceptibility of various other cancers such as breast cancer [35], ovarian cancer [36,37], uterine cervical cancer [38], and colorectal cancer [39] have also been reported, thus substantiating the crucial role of this protein in cancer. Previous study from our lab on oral cancer risk found the significant influence of another RB1 polymorphism, rs3092904, on oral cancer susceptibility [23].…”
Section: Discussionmentioning
confidence: 78%
“…However, further studies elucidating the downstream effects of this polymorphism are warranted. The effect of RB1 polymorphisms on the susceptibility of various other cancers such as breast cancer [35], ovarian cancer [36,37], uterine cervical cancer [38], and colorectal cancer [39] have also been reported, thus substantiating the crucial role of this protein in cancer. Previous study from our lab on oral cancer risk found the significant influence of another RB1 polymorphism, rs3092904, on oral cancer susceptibility [23].…”
Section: Discussionmentioning
confidence: 78%
“…The SNP (rs11515 -C98A) CDKN2A gene determines a non-synonymous serine-to-arginine substitution located in the 3 0 -UTR of exon 3 (36). In fact, similarly, we observed for s-MTC, CDKN2A gene rs11515 polymorphism was also considered a protective factor against cervical cancer (35). CDKN2A gene (rs11515) polymorphism may affect the DNAbinding zinc finger motif, thus modifying p21 expression and function (37).…”
Section: European Journal Of Endocrinologymentioning
confidence: 80%
“…CDKN2A gene polymorphisms have largely been investigated in different types of cancers (20,22,35). The SNP (rs11515 -C98A) CDKN2A gene determines a non-synonymous serine-to-arginine substitution located in the 3 0 -UTR of exon 3 (36).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…By contrast, a study by Geddert et al (30) indicated that these polymorphisms had no association with upper gastrointestinal and oesophageal adenocarcinomas. Previous studies have shown that these polymorphisms are associated with the progression of ovarian and upper gastrointestinal cancers, despite uncertainty regarding the progression of cervical cancer (31,32). A study by Chen et al (33) reported that in patients with the polymorphic genotype for C540G there was no significant increase in the hazard ratio (HR) for the age-related pancreatic cancer risk, as compared with those with wild-type genotype [HR, 0.80; 95% confidence interval (CI): 0.56-1.17] and there was a only a marginally significant increase in the HR for C580T (HR, 1.52; 95% CI: 1.00-2.30).…”
Section: Discussionmentioning
confidence: 99%